Perancangan Sistem Deteksi Vena Pada Punggung Tangan Berbasis Inframerah Untuk Sistem Biometrik - Fitriya Fitriya (Universitas Airlangga, 2019)
AbstractVein detection is one of the imaging techniques required for biometric authentication purposes. The vein is chosen as an object because of its strength in terms of universality and uniqueness especially in adults because the venous pattern will only change slightly with age and each person has a different pattern, besides from the object side, the veins have no influence from temperature and humidity, and physical contactless with the other user. The purpose of this research is to create design that can visualize the veins as well and determine the optimum parameters to produce a better quality of vein image than the original image. The data for this research were obtained from 10 naracoba people who were varied of Boddy Mass Index and skin pigment. From the research, dorsal hand vein visualization tool for biometric system has been successfully designed using 726 nm infrared LED and image processing by convert of image to grayscale, image sharpening, histogram equalisation until segmentation by local thresholding method and the optimum parameters obtained to obtain a good image based on contrast analysis in this study is with a distance of 6 cm exposure.Keyword : Vein Detection, Biometrik, Near Infrared, Segmentation